Performance Management and Quality Culture Reflection towards the Professional Teachers of the ASEAN Economic Community Era - Serli Serli (Ta'dib: Jurnal Pendidikan Islam, 2017)
Educational problems are so complex. It spurs so fast and moves dynamically through time and place, and those which are stagnant and rigid will be crushed. What Umar bin Khattab has said, "Educate your son according to his time" indicate that education moves over the times and places that continually change, and it necessitates renewal in all aspects, reinforced by the circumstance that today all information is easily accessed from the virtual world due to technological advances so that innovation becomes imperative. The organizational quality culture cannot be denied. It is last guardian of the continuity of education in addition to continuous improvement on the quality of educators. Otherwise, though not obvious, there will be a substitution of players with tight competition as globalization spreads in every sector. Every society knows that it is the education as a pioneer. Quality is not accidental work. It is sustained by the curriculum and educational system, and most importantly the professionalism of educators, for being the spearhead creators of creative, skilled and innovative resources, because people who truly have expertise (skilled labor) will survive in the ASEAN market, and hopefully Indonesian teachers can be ones